Applications of topological derivative for accelerating the genetic algorithm in shape optimization of coupled models - Novotny, Antonio; Szulc, Katarzyna; Żochowski, Antoni (Instytut Badań Systemowych. Polska Akademia Nauk, 2012)
The paper considers a new variant of the genetic algorithm for finding the location and size of small holes in the domain, in which the coupled linear and non-linear boundary value problems are defined. The linear and non-linear parts are connected by the transmission condition on the common boundary. The expansion of the shape functional for non-linear part and the expansion of Steklov-Poincare operator for linear part are provided in order to determine the form of topological derivative for the coupled model. The value of topological derivative is then used for computing the probability density applied later in generating location of holes by the genetic algorithm.
35 stron ; 21 cm
Bibliografia s. 29-32
Keywords: Genetic algorithm; Algorytm genetyczny; Optymalizacja kształtu; Shape optimization; Topology optimization; Optymalizacja topologii